Business Law - David Kelly; Ruby Hammer; John Hendy (New York Routledge, 2018)
Business Law offers comprehensive coverage of the key aspects of business law that is easy to understand for both law and non-law students. Established legal topics such as the English Legal System, Contract, Consumer, Company and Employment Law, as well as emerging areas such as Health and Safety and Environmental Law, are considered as they apply to business. This edition also includes coverage of the now essential field of Intellectual Property, written by Janice Denoncourt. The work has been thoroughly updated to include all the recent major developments in the law, such as the Consumer Rights Act 2015 and the Small Business, Enterprise and Employment Act 2015 together with important cases that have been decided in the period since the last edition. Mention, of course is made of Brexit, although as yet its outcome and consequences remain uncertain. Key learning features include: Law in context boxes that contextualise each chapter's topic within the Business environment; diagrams and tables to illustrate key principles; updated key case boxes that highlight landmark cases for easy reference; revision summaries at the end of each chapter to help clarify the key points for each topic; an attractive two-colour text design that aids easy understanding and quick referencing; an up-to-date and easy-to-use companion website with additional features to further your learning and track your progress. Business Law offers a topical overview of this subject in an accessible style suited to both law and business studies undergraduates.
Keywords: Commercial law; Law and legislation; Labor laws; Business enterprises; (ASB-2400) Law for Business